2018
DOI: 10.1128/aac.00398-18
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter cloacae Complex Isolated from Shrimps from Vietnam Carrying bla IMI-1 Resistant to Carbapenems but Not Cephalosporins

Abstract: I n August 2017, batches of Penaeus monodon (Asian tiger shrimp) and P. vannamei (White leg shrimp), originating from fish farms in Vietnam, were screened for the presence of carbapenemase-producing Enterobacteriaceae (CPE). An Enterobacter cloacae complex was isolated on a Chrom ID carba plate (bioMérieux Benelux BV), designated 3568. Susceptibility testing was performed according to ISO 20776-1:2006 with Sensititre panels EUVSEC and EUVSEC2 (Thermo Fisher, Waltham, MA, USA). Results are shown in Table 1. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…We isolated a bla IMI-1 -harbouring E . coloacae complex from fish and water spinach, which is usually cultivated in water-rich regions, corroborating previous reports that associated these bacteria with aquatic environments 6,21,22 . Of note, we isolated two water spinach isolates of the same ST and EcloIMEX type from different districts, suggesting the existence of a shared reservoir of bla IMI-1 dissemination.…”
Section: Discussionsupporting
confidence: 90%
“…We isolated a bla IMI-1 -harbouring E . coloacae complex from fish and water spinach, which is usually cultivated in water-rich regions, corroborating previous reports that associated these bacteria with aquatic environments 6,21,22 . Of note, we isolated two water spinach isolates of the same ST and EcloIMEX type from different districts, suggesting the existence of a shared reservoir of bla IMI-1 dissemination.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the public health importance of carbapenemase-producing E. coli and/or Salmonella, both as pathogens and as vectors for resistance mechanisms there is a need to follow further developments in this area for farm animals and food derived thereof. Especially as carbapenemase-producing Enterobacteriaceae has been reported, not only in farm animals and food derived thereof but also from vegetables from many parts of the world including Europe (Zurfluh et al, 2015;Touati et al, 2017;Brouwer et al, 2018;K € ock et al, 2018;Liu et al, 2018;Irrgang et al, 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Often, these genes are chromosomally located in nonpathogenic aquatic bacterial species, limiting them as relevant threats for the general population (3). However, more recent studies screening seafood imported from Southeast Asia have found carbapenemases encoded in human pathogens or on conjugative plasmids (46). As such, seafood imported from countries with high carbapenemase prevalence may need to be included in monitoring programs.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins with carbapenemase activity fall into the three major Ambler classes A, B, and D β-lactamases (7). Genes of these classes have been described on mobile genetic elements, such as plasmids and chromosomally integrated elements, which adds to the concerns regarding these genes because they facilitate the spread of these genes among both commensal and pathogenic bacteria (6, 8, 9). The family of Enterobacteriaceae consists of many commensal, opportunistic, and infectious species that can readily exchange genetic material.…”
Section: Introductionmentioning
confidence: 99%